Using hospital-based studies of community-onset bloodstream infections to make inferences about typhoid fever incidence - Marchello, Christian S. (Trop Med Int Health, 2019)
OBJECTIVES: Hospital-based studies of community-onset bloodstream infections (CO-BSI) are less resource-intensive to carry out than population-based incidence studies. We examined several metrics capturing the potential role of Salmonella Typhi as a cause of CO-BSI for making inferences about incidence. METHODS: We systematically reviewed three databases for hospital-based studies of CO-BSI. We determined, by study, the prevalence and rank order of Salmonella among pathogenic bloodstream isolates, and the prevalence ratio of Salmonella Typhi to Escherichia coli (S:E ratio). We then describe these hospital-based study metrics in relation to population-based typhoid fever incidence data from a separate systematic review. RESULTS: Forty-four studies met the inclusion criteria, of which 23 (52.3%) isolated Salmonella Typhi at least once. Among studies isolating Salmonella Typhi, the median (interquartile range) prevalence and rank order of Salmonella Typhi compared to other pathogens isolated in BSI was 8.3% (3.2–37.9%) and 3 (1–6), respectively. The median (interquartile range) S:E ratio was 1.0 (0.4–3.0). With respect to incidence, in Pemba Island, Tanzania, prevalence, rank order, S:E ratio, and incidence was 64.8%, 1, 9.2 and 110 cases per 100 000, respectively, and in Boulkiemdé, Burkina Faso, was 13.3%, 3, 2.3 and 249 cases per 100 000. CONCLUSIONS: We describe considerable variation in place and time for Salmonella Typhi prevalence, rank order, and S:E ratio among hospital-based studies of CO-BSI. Data from simultaneous typhoid prevalence and incidence studies are limited. We propose that hospital-based study metrics warrant evaluation for making inference about typhoid incidence and as covariates in typhoid incidence models.